PELATIHAN PAPERLESS ACCOUNTING DAN PERPAJAKAN MENGGUNAKAN SOFTWARE ACCURATE ONLINE - Safri; Saur Simamora (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Accounting learning at Sumpah Pemuda Vocational School is carried out by utilizing practice questions from UKK SMK, where the question sheets are reproduced by printing or photocopying, for this it is necessary to carry out training and introduction to the paperless concept. This activity aims to introduce the go green-go paperless concept in processing accounting transaction data so that it can present financial reports, using the Accurate Online Accounting system application and supported by a Windows application that integrates basic accounting and taxation. From the training that has been carried out, the go green-go paperless concept can be implemented well, there has been an increase of 100% of participants creating Accurate online accounts, 92% of participants have started to get to know the application, and 61% of participants have understood how the application works. The problems that arise during the activity are minor problems in the form of unstable internet, short activity implementation time, a fairly large class number of participants, and only completing 1 (one) transaction case